MENGEKSPLOR BAKAT DAN MINAT SISWA MELALUI RAGAM SENI DI SEKOLAH DASAR - Atmijaya, Rakhmatika; Andaryani, Eka Titi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Exploring students' talents and interests through various arts in elementary schools (SD) is research using the qualitative research method "Case Study Research". This research aims to make it easier for teachers to observe and recognize students' talents and interests and develop them in the art field chosen by the students. This research was carried out using data collection techniques through interview, observation and documentation instruments. Exploring students' talents and interests through various arts is carried out at SD Negeri Kedungsukun 01, Adiwerna District, Tegal Regency, with three areas of arts study added to the school's extracurricular activities, namely music, dance and fine arts. The results of this research show that the areas of art study at SD Negeri Kedungsukun 01, Adiwerna District, Tegal Regency that are of interest to students are 40% fine arts, 30% musical arts, and 30% dance arts. From this data, it is stated that the fine arts field of study is more popular with students, the second is music arts, and the third is dance arts.